Implementation of the Supplementary Feeding Program for Toddlers Experiencing Stunting - Elsa Octavia Bessie; Petrus Kase; Adriana Fallo; Wijayanti, Nadia Sasmita (Universitas Terbuka, 2025)
Stunting is a chronic nutritional disorder resulting from prolonged inadequate nutrient intake, leading to impaired physical growth, delayed cognitive and motor development, and increased risk of metabolic disorders in children. Addressing stunting is a public health priority in Indonesia, particularly in rural areas where food security and health services are often limited. This study aims to describe and analyze the implementation of the Supplementary Feeding Program (SFP) for stunted toddlers in Lalukoen Village. Using a qualitative research method with a descriptive approach, data were collected through interviews, observations, and documentation. The findings reveal that the SFP implementation in Lalukoen Village has been largely ineffective. Key challenges include minimal parental involvement during socialization, as nutritionists did not adequately engage or educate families.Additionally, the low participation of community health cadres, misalignment between the food and the children’s nutritional needs, limited program budgets, and the absence of food processing infrastructure provided by the village government further constrained program effectiveness. This study highlights the urgent need to improve community-based nutrition interventions through inclusive engagement strategies, particularly by actively involving parents in early program planning and implementation stages. Furthermore, strengthening logistical and infrastructure support, especially for food preparation and distribution, is essential to improving outcomes. The research contributes to the discourse on local public health governance by offering practical recommendations for enhancing the effectiveness of stunting prevention programs in rural settings, with broader implications for policy and program design in similar contexts.